Inclusive Higher Education in India in the Age of Neo-Liberalism - Manas Behera (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2021)
Education is now considered a pre-condition in all societies, particularly in the developing societies, for inclusive development and to fight different inequalities. This can only be possible if access to higher education is based on equity, and a public-funded education system can ensure this. The paper is based on qualitative research and analyses the changes in the higher education system in India from a largely public funded education system towards a commercial, profit-driven system. The policy shifts are analyzed from comparative and historical perspectives. The neo-liberal approach to education facilitates commercialization,leading to the exclusion of the poor from the higher education system and defeating the constitutional goals of building an inclusive democratic society. The functioning of democracy is also dependent on education as it creates citizens and empowers the marginalized to enter into the democratic system, thus legitimizing the state. The paper concludes that the neo-liberal paradigm of development is contradictory to inclusive education and inclusive development as it commoditizes education.